PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN WISATAWAN NUSANTARA DI DAYA TARIK WISATA KEBUN RAYA “EKA KARYA” BALI - Jayadi, Angga Suputra; Sasrawan Mananda, I GPB.; Oka Karini, Ni Made (Jurnal IPTA (Industri Perjalanan Wisata), 2023)
This study aims to determine the effect of service quality and facilities on the satisfaction of domestic tourists in the tourist attraction of the "Eka Karya" Botanical Gardens in Bali. The sampling technique in this study was taken by accidental sampling with a sample size of 100 respondents, the respondents of this research were tourists who were visiting or had visited the tourist attraction of the "Eka Karya" Botanical Gardens in Bali. Meanwhile, this research is quantitative in nature by using the method of multiple linear regression analysis as a data analysis technique. In this study using data collection techniques, namely library research, interviews, observations and distributing questionnaires to obtain data. The results of the multiple linear regression analysis based on the delta test of the coefficient of determination resulted in an R Square of 0.709, meaning that 70.9% of tourist satisfaction can be explained by the variables of service quality and facilities. While 29.1% of tourist satisfaction is influenced by other variables that are not included in this research model. This means that the quality of services and facilities affects the satisfaction of tourists visiting the tourist attraction of the Bali "Eka Karya" Botanical Gardens, the better the quality of services and facilities, the higher the level of satisfaction of visiting tourists.